2012
DOI: 10.1021/es300574u
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Primary Marine Aerosol Properties: CCN Activity of Sea Salt and Mixed Inorganic–Organic Particles

Abstract: Sea spray particles ejected as a result of bubbles bursting from artificial seawater containing salt and organic matter in a stainless steel tank were sampled for size distribution, morphology, and cloud condensation nucleus (CCN) activity. Bubbles were generated either by aeration through a diffuser or by water jet impingement on the seawater surface. Three objectives were addressed in this study. First, CCN activities of NaCl and two types of artificial sea salt containing only inorganic components were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 66 publications
6
85
0
Order By: Relevance
“…However, no clear difference was seen between the first (when the microlayer was present) and subsequent size distributions during a given microlayer enriched experiment. In past experiments, the addition of organics to bubbling experiments have shown changes in the size distribution (Sellegri et al, 2006), particle number concentration (Fuentes et al, 2010b;King et al, 2012;Tyree et al, 2007), and CCN activity Atmos. Chem.…”
Section: Activation Diametermentioning
confidence: 99%
See 3 more Smart Citations
“…However, no clear difference was seen between the first (when the microlayer was present) and subsequent size distributions during a given microlayer enriched experiment. In past experiments, the addition of organics to bubbling experiments have shown changes in the size distribution (Sellegri et al, 2006), particle number concentration (Fuentes et al, 2010b;King et al, 2012;Tyree et al, 2007), and CCN activity Atmos. Chem.…”
Section: Activation Diametermentioning
confidence: 99%
“…Sellegri et al (2006) saw a log-normal mode amplitude shift towards smaller diameters with the addition of sodium dodecyl sulfate (SDS) to artificial seawater; Fuentes et al (2010b) observed similar behavior in tests with artificial seawater and biogenic exudates, while King et al (2012) saw an additional lognormal mode at 200 nm with the addition of organic material to artificial seawater. Water temperature has also shown an effect on aerosol size distribution and number concentration, though different groups have seen varying trends.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…[63] Nevertheless, large uncertainties in the number Credit: Surface Ocean-Lower Atmosphere Study Law SOLAS research directions production flux remain, [63] although recent results converge within a factor of 2-3. [75] Advances have also been made in our understanding of the effect of ocean-derived aerosols on climate, particularly with respect to the effects of OM on CCN production, [76][77][78] and on boundary layer chemistry. [79][80][81] There has also been recent recognition that particles of ,1 mm may be a significant source of CCN in marine regions, [70] that is potentially more important than the contribution from the oxidation of DMS.…”
Section: Sea Spray Bubblesmentioning
confidence: 99%